Part-time employment: a comparative analysis of Spain and the Netherlands - Blázquez Cuesta, Maite; Ramos Martín, Nuria Elena (Amsterdam, 2007)
"Most industrialized countries have seen part-time employment as a percentage of total employment increase in the last decade. This paper presents the results of a comparative study of part-time employment in Spain and the Netherlands. The project comprised a legal comparative study of the effectiveness of the normative solutions provided by the Dutch and Spanish legal orders regarding the protection of part-time workers and the promotion of part-time employment, with special attention paid to the gender dimension of part-time work in both countries; and an analysis, based on data extracted from the European Community Household Panel (1995-2001), of the determinants of part-time employment in both countries and an examination of the extent to which part-time jobs are used as stepping-stones to full-time positions. We found significant country differences regarding females’ decisions to take part-time jobs. We also found that, in general, Dutch females are not less likely than their male counterparts to increase the number of hours they work. However, this applies only to those females who are part of a couple or have children younger than 12 years. In Spain, females are 2.6 times less likely than their male counterparts to switch from a part-time to a full-time job."